SPECIFIC UPTAKE OF MONOCLONAL ANTIBODYCONJUGATED METHOTREXATE BY HUMAN LYMPHOCYTIC LEUKEMIC B CELLS - Zhu, Zhenping; Yang, Chunzheng; Ghose, Tarunendu; Kralovec, Jaroslav (Chinese Journal of Cancer Research, 2013)
Objective: To analysis the uptake of free MTX and MTX conjugated to tumor specific monoclonal antibody by target and non-target cells. Methods: The folate antagonist methotrexate (MTX) was conjugated to two monoclonal antibodies (Mab) directed against human chronic lymphocytic leukemia (CLL), Dal B01 and Dal B02, by an active ester method. Both conjugates were more cytotoxic toward the target tumor cell line D10-1 than to the non-target cell line MOLT-3, and Dal B02- MTX conjugate was more inhibitory to D10-1 cells than free MTX in a 6 h pulse exposure assay. Results: Drug uptake studies revealed that D10-1 cells took up much more Dal B01 and Dal B02-conjugated MTX than free MTX. The amounts of drug taken up by D10-1 cells incubated with Dal B01 and Dal B02-conjugated MTX were always 3 to 5-fold higher than that taken up by MOLT-3 cells, although the latter took up more drug when incubated with free MTX. Furthermore, tumor cells incubated with Dal B01 or Dal B02-conjugated MTX retained much larger amounts of drug for a prolonged period of time than those incubated with free MTX. Conclusion: The enhanced specific cytotoxicity of Dal B01 and Dal B02-MTX conjugates toward target tumor cells is therefore likely due to (I) delivery of larger amounts of MTX to target cells when the drug is conjugated to Mab; (ii) longer retention of Mab-conjugated MTX by target cells; and (iii) slow, prolonged release of MTX from the surface-bound or endocytosed conjugates, rendering them into a sustained release dosage form.